Case Report: Creeping Growth in Lymphoplasmacyte-Rich Meningioma—A Radiologic Variant - Li, Jiuhong; Zan, Xin; Feng, Min; Deng, Xueyun; Zhang, Si; Liu, Wenke (Frontiers in Surgery, 2021)
Lymphoplasmacyte-rich meningioma (LRM) is a rare histologic subtype of meningioma. Creeping-growth pattern is uncommon in meningioma, and the mechanism is unclear. Here, we report a 44-year-old man presented with extremities weakness for 2 months and incontinence for two weeks. Head and neck magnetic resonance imaging revealed diffuse creeping-growth nodular meningeal masses with skull base, tentorium, sella area, and C1-6 vertebral plane involvement. An operation was carried out, cervical and lower clivus part of the lesion was resected, however, gross total resection could not be achieved due to the wide-spread lesions. Pathologic examination revealed the diagnosis of LRM. The patient is free from progression clinically 3 months postoperatively. We also conducted a systematic literature review about LRM with creeping-growth pattern. A total of only 9 cases (including the present case) of creeping-growth LRMs were included and analyzed in terms of clinical manifestations, radiological features, treatment and outcome. LRMs show a higher rate (7.5%) of creeping growth pattern than other types of meningioma. The average creeping length of all creeping-growth LRMs was 11.4±10.9 cm (range, 3-30cm). Most cases (66.7%) had obvious peritumoral edema. Total removal rate is low (33.3%) and two of them (22.2%) received biopsy, followed by steroids treatment (or further immunosuppressive drugs therapy) and radiotherapy. The recurrence rate is higher than conventional LRMs (22.2% vs. 11.3%) and one patient (11.1%) died 11 months after treatment. Creeping-growth pattern in LRM may be considered as a general radiologic variant. The recurrence rate is higher compared with LRM with round/swelling pattern. We speculated that the pathogenesis of creeping-growth in LRM may be associated with damage of lymphatic systems of central nervous system.